DNA polymorphism at locus-2 of growth hormone gene of Madura cattle - AGUS PURWOKO; SUTARNO SUTARNO; NITA ETIKAWATI (Society for Indonesian Biodiversity, 2003)
The objectives of the research were to detect DNA polymorphism at locus 2 of bovine growth hormone gene of Madura cattle and to know its genetic diversity. DNA polymorphisms and their effect on phenotypic traits have been studied widely in dairy cattle but not for beef cattle, especially for Indonesian local cattle. Polymorphism was detected using PCR-RFLP using primer GH-5 and GH-6 for amplifying locus 2 of growth hormone gene. Genetic diversity was analyzed based on the formula of Nei (1973, 1975). DNA polymorphism was found on locus 2 of growth hormone gene using MspI restriction enzyme. This polymorphism may be caused the lost of restriction MspI site. The genetic diversity was 0.4422.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: bovine growth hormon gene, PCR-RFLP, polymorphism, Msp I restriction enzyme, Madura Cattle.